Neuromuscular responses to conditioned soccer sessions assessed via GPS-embedded accelerometers: Insights into tactical periodization - Buchheit, M.; Lacome, M.; Cholley, Y.; Simpson, B. M. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To examine the reliability of field-based running-specific measures of neuromuscular function assessed using global positioning system (GPS)-embedded accelerometers and their responses to 3 typical conditioned sessions (ie, strength, endurance, and speed) in elite soccer players. Methods: Before and immediately after each session, vertical jump (countermovement jump [CMJ]) and adductor squeeze strength (groin) performances were recorded. Players also performed a 4-min run at 12 km/h followed by four ~60-m runs (run=12 s, r=33 s). GPS (5 Hz) and accelerometer (100 Hz) data collected during the 4 runs and the recovery periods, excluding the last recovery period, were used to derive vertical stiffness (K), peak loading force (peak force over all the foot strikes [Fpeak]), and propulsion efficiency (ie, the ratio between velocity and force loads [Vl/Fl]). Results: Typical errors were small (CMJ, groin, K, and Vl/Fl) and moderate (Fpeak), with moderate (Fpeak), high (K and Vl/Fl), and very high ICCs (CMJ and groin). After all sessions, there were small decreases in groin and increases in K, but changes in F were all unclear. By contrast, the CMJ and Vl/Fl ratio responses were session dependent. There was a small increase in CMJ after speed and endurance, but unclear changes after strength; the Vl/Fl ratio increased substantially after strength, but there were a small and a moderate decrease after endurance and speed, respectively. Conclusions: Running-specific measures of neuromuscular function assessed in the field via GPS-embedded accelerometers show acceptable levels of reliability. Although the 3 sessions examined may be associated with limited neuromuscular fatigue, changes in neuromuscular performance and propulsion efficiency are likely session-objective dependent.